Conditionally Amplifiable BACs: Switching From Single-Copy to High-Copy Vectors and Genomic Clones - Wild, Jadwiga; Hradecna, Zdenka; Szybalski, Waclaw

(untitled) (Genome Research, 2002)
The widely used, very-low-copy BAC (bacterial artificial chromosome) vectors are the mainstay of present genomic research. The principal advantage of BACs is the high stability of inserted clones, but an important disadvantage is the low yield of DNA, both for vectors alone and when carrying genomic inserts. We describe here a novel class of single-copy/high-copy (SC/HC) pBAC/oriV vectors that retain all the advantages of low-copy BAC vectors, but are endowed with a conditional and tightly controlled oriV/TrfA amplification system that allows: (1) a yield of ∼100 copies of the vector per host cell when conditionally induced with l-arabinose, and (2) analogous DNA amplification (only upon induction and with copy number depending on the insert size) of pBAC/oriV clones carrying >100-kb inserts. Amplifiable clones and libraries facilitate high-throughput DNA sequencing and other applications requiring HC plasmid DNA. To turn on DNA amplification, which is driven by the oriV origin of replication, we used copy-up mutations in the gene trfA whose expression was very tightly controlled by thearaC–P